2016
DOI: 10.1002/cbic.201600066
|View full text |Cite
|
Sign up to set email alerts
|

The Conformational Variability of FimH: Which Conformation Represents the Therapeutic Target?

Abstract: FimH is a bacterial lectin found at the tips of type 1 pili of uropathogenic Escherichia coli (UPEC). It mediates shear-enhanced adhesion to mannosylated surfaces. Binding of UPEC to urothelial cells initiates the infection cycle leading to urinary tract infections (UTIs). Antiadhesive glycomimetics based on α-d-mannopyranose offer an attractive alternative to the conventional antibiotic treatment because they do not induce a selection pressure and are therefore expected to have a reduced resistance potential.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 66 publications
(75 reference statements)
0
25
0
Order By: Relevance
“…Some of the mutations reported here, such as V27A, N70S, and S78N, have been previously reported in UPEC strains. These polymorphisms are considered to be potential patho-adaptations that may confer significant advantages in regards to bacterial epithelial colonization (Eris et al, 2016). Such patho-adaptative polymorphisms were also observed in E. coli strains obtained from pediatric patients with inflammatory bowel disease (IBD) (Iebba et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Some of the mutations reported here, such as V27A, N70S, and S78N, have been previously reported in UPEC strains. These polymorphisms are considered to be potential patho-adaptations that may confer significant advantages in regards to bacterial epithelial colonization (Eris et al, 2016). Such patho-adaptative polymorphisms were also observed in E. coli strains obtained from pediatric patients with inflammatory bowel disease (IBD) (Iebba et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, ligand or mannoside binding to FimH shifts its pre-existing equilibrium toward the high-affinity R state while occluding the mannose binding pocket and inhibiting host-pathogen interactions. Reports from several other groups [54-55, 93-94]postulate that urine flow in the bladder kinetically selects the rapidly-associating low-affinity conformation of FimH for receptor binding and that shear stress converts this bound low-affinity conformation to a bound high-affinity conformation of FimH. While the in vivo relevance of shear stress to human UTI remains unclear, these structural studies suggest that mannosides can in fact target both the low-affinity T state in addition to the high-affinity R state.…”
Section: X-ray Structure Guided Design Of Monovalent O-mannoside mentioning
confidence: 99%
“…These studies are based on only a few FimH mannoside ligands[54], but the data suggests that individual mannosides can bind to these different states with significantly different affinities, while others bind with equal affinity to both the high affinity R and low affinity T conformations. It has also been shown that mannosides can bind with different affinities under “flow” or “non-flow” conditions as determined from in vitro assays [95-97].…”
Section: X-ray Structure Guided Design Of Monovalent O-mannoside mentioning
confidence: 99%
“…Intermediate states and a high variability of the conformational ensemble have been described . Although all conformational states of FimH play a relevant role for the pathogenicity of UPEC, efforts for the development of therapeutic FimH antagonists have almost exclusively been focused on the high‐affinity state of the protein …”
Section: Introductionmentioning
confidence: 99%